The Effect of the 3I’s Method (Instruct, Integrate, Involve) on Students’ Recount Text Writing Skill at a Vocational High School - Indriyani Adam; Zulfah Fakhruddin; Abd. Haris Sunubi; Muajiz Muallim (Journal of English Language and Education, 2026)
This study was conducted to examine the effectiveness of the 3I’s method (Instruct, Integrate, and Involve) in enhancing students’ ability to write recount texts at SMK Negeri 2 Parepare. A quasi-experimental research design was employed, involving both experimental and control groups that completed pre-tests and post-tests. The participants were eleventh-grade students, and the sample was selected through cluster random sampling. Class XI DKV C served as the experimental group, while Class XI TITL B functioned as the control group, with 21 students in each class. Data were collected using a recount writing test evaluated according to five writing components: content, organization, vocabulary, language use, and mechanics, based on Heaton’s scoring rubric. The collected data were analyzed using descriptive statistics and an independent samples t-test. The findings revealed that the experimental group achieved a higher mean post-test score (86.05) than the control group (81.52). In addition, the statistical analysis produced a significance value of 0.029, which was lower than the 0.05 threshold, indicating a significant difference between the groups. These results suggest that the 3I’s method effectively improves students’ recount writing performance, particularly in generating ideas, applying grammar accurately, and producing well-organized texts. Therefore, the 3I’s method can be recommended as an effective instructional approach for teaching writing in vocational high school settings.